Rancang Bangun dan Uji Performansi Alat Pembubur Buah Tomat untuk Saos (Design and Performance Test Blander Tool for Fruit Tomato Sauce): Design and Performance Test Blander Tool for Fruit Tomato Sauce - Amuddin Amuddin; Rahmat Sabani (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2016)
This study aims to (1) Design and construct tomatoes blander tool for sauce through systematic stages; (2) Determine the efficiency of the appliance with an emphasis on power and effectiveness of the cutter blade; (3) Test the technical performance of the blander tool for tomato sauce that is more specific in terms of technical (engineering). The benefits of this research are (1) Addressing the excess (surplus) of tomatoes and other fruits; (2) Scientific Knowledge in Design blander tool for tomatoes and is also used as fruit crusher on other fruits; (3) Contributions for science and technology development, especially engineering design tools and machinery. This research was conducted at the Laboratory of Agricultural Engineering Faculty of Food and Agroindustrial Technology, University of Mataram. Method used in this study was an experimental method that experiments conducted on a direct observation or an investigation is planned to obtain data as the results of experiments that should be studied in depth through performance equipment being tested. Parameter research with the treatment variations in rotational speed of the blade of (1) Rotational blade 660 rpm; (2) Rotational blade 670 rpm; (3) Rotational blade 680 rpm; (4) Rotational blade 690 rpm; (5) Round blade 700 rpm and data retrieval is done every five replications. The results showed (1) input capacity designed based on feedback obtained mass velocity bulk density of the tomatoes with a value of 432.7798 kg/m3 and the resulting standard deviation of 0.8606 kg/m3; (2) The amount of power usage based on the calculation amounted to 129.417 Watt with a rotational blade at 700 rpm with mechanical efficiency of 69 391%; it can be proven that the use of smaller power in the construction of power design. (3) The blade rotation (rpm) on tomatoes blander for the engine design results significantly influence the speed of entry materials, speed of working time, total dissolved solids and viscosity, but did not significantly affect the output flow rate and the amount of accumulated material.